2022
DOI: 10.1016/j.bonr.2021.101164
|View full text |Cite
|
Sign up to set email alerts
|

Sex-specific differences in direct osteoclastic versus indirect osteoblastic effects underlay the low bone mass of Pannexin1 deletion in TRAP-expressing cells in mice

Abstract: Pannexin1 (Panx1) is a hemichannel-forming protein that participates in the communication of cells with the extracellular space. To characterize the role of osteoclastic Panx1 on bone, Panx1 fl/fl ;TRAP-Cre (Panx1 ΔOc ) mice were generated, and compared to Panx1 fl/fl littermates at 6 weeks of age. Total and femoral BMD was ~20% lower in females and males whereas spinal BMD was lower only in female Panx1 ΔOc mice. μCT a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…This raises the possibility that at least part of the skeletal muscle phenotype observed in the global Panx1 KO mice could result from Panx1 deletion in cells other than skeletal muscle. More recently, it has been reported that Panx1 has sex‐dependant roles in regulating the number of osteoclasts, cells required for bone resorption (Deosthale et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…This raises the possibility that at least part of the skeletal muscle phenotype observed in the global Panx1 KO mice could result from Panx1 deletion in cells other than skeletal muscle. More recently, it has been reported that Panx1 has sex‐dependant roles in regulating the number of osteoclasts, cells required for bone resorption (Deosthale et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“… 115 This evidence suggests that alterations in the osteoclast secretome lead to reduced osteoblast function and low bone mass in male Panx1-deficient mice. 115 …”
Section: Panxs In Musculoskeletal Systemmentioning
confidence: 99%
“…114 McCutcheon et al found that both female and male Panx1-deficient mice had significantly reduced cancellous bone in the distal femur and lumbar spine, with higher osteoclast activity observed in female Panx1-deficient mice, while there was no change in males. 115 Conversely, Panx1-deficient mice exhibited higher osteoclast differentiation and in vitro osteoclast bone resorption activity. 115 This evidence suggests that alterations in the osteoclast secretome lead to reduced osteoblast function and low bone mass in male Panx1-deficient mice.…”
Section: Panxs In Musculoskeletal Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, TRAP-specific Panx1 KO mice (osteoclast cells) had higher rates of bone resorption, reduced formation, and a resultant lower trabecular bone mass in female mice [82]. This would suggest PANX1 function in osteoclasts is necessary to ensure proper coupling between bone formation and resorption, while in osteocytic-specific Panx1 KO mice, bone mineral density, after reaching skeletal maturity, is higher in female KO mice than in wild-type mice.…”
Section: Bonementioning
confidence: 99%